Simulation on daylighting penetration into building atrium for artificial intelligence intergrated farming / Mohd Ezamil Mazlan, Ts. Azlan Ariff Ali Ariff and Dr. Zalina Samadi - Mazlan, Mohd Ezamil; Ali Ariff, Azlan Ariff; Samadi, Zalina (College of Built Environment, 2023)
Urban farming in characterised as mostly taking place in a community within a city or other densely populated urban settings.